The Methodological Component of Improving the Assessment of Long-Term Debt as a Financial Instrument - Yevheniia Popko; Olha Lukova (Облік і фінанси, 2023)
Accounts receivable and payable are one of the most common types of financial instruments of agricultural enterprises. Until recently, such debt was considered a traditional accounting object with established recognition rules, cost measurement and disclosure. However, since the end of 2019, the valuation of such financial instruments has changed due to introducing the present value as a priority for its long-term type. The article aims to reveal the methodology for determining the present value of long-term debt as the most common type of financial instrument. The specifics of the application of the present value for the assessment of long-term debt were disclosed. It was substantiated which types of such debt are subject to the discounting requirement and which are not. The problem points of introducing a new type of assessment, which affect the data of financial statements, were identified. The article contains the necessary data and rules for the most reliable calculation of the present value of long-term receivables and long-term liabilities as financial instruments. The study results show that for the most accurate and objective determination of the present value of long-term receivables and long-term liabilities as financial instruments, the agricultural enterprise needs to record the methodology of cost measurement of such objects in the Regulation of accounting policy. In particular, it is necessary to specify the object (which type of long-term debt is subject to discounting and which is not), the calculation (formula), the variable (discounting rate selection procedure) and the documentary (a form of the primary document) components.